Realization and Contribution Sukuk Retail, Savings, and Retail's Waqf During The 2020 Covid-19 Pandemic - Moh Agus Nugroho; Rika Febby Rhamadhani; Fathul Khair (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
Covid-19 entered Indonesia around March 2020, having an impact on economic growth. Indonesia during 2020 minus 2.07 percent of its economy. This economic decline was caused by Covid-19 which had an impact on the economic activities of residents. Throughout 2020 the government issued 4 series of Sukuk, retail Sukuk SR0012 and SR013, savings Sukuk series ST007 and finally retail Sukuk waqf SWR001. The purchase realization of SR012 was IDR 12,142 trillion, and SR013 was IDR 25,667 trillion. Then ST007, the funds that were collected were Rp. 5.18 trillion and the retail Sukuk waqf series SWR001 as much as Rp. 14.91 billion. Despite the minus economy, the Sukuk is still in demand by the Indonesian people. For own contribution, retail Sukuk funds are used for infrastructure development such as bridges, Hajj boarding buildings, construction of railroads, and others. Meanwhile, savings Sukuk are allocated for economic recovery and eligible green projects. Finally, retail waqf Sukuk is used for financing social activities and empowering people, such as the construction of an eye hospital for the poor and others.